A political economy of Lebanon, 1948-2002 : the limits of laissez-faire - Gaspard, Toufic K. (Social, economic, and political studies of the Middle East and Asia ;, 2004)
This work assesses Lebanon's development experience during 1948-2002, a case study of laissez-faire performance over more than 50 years. The text analyzes the strong monetary crisis of the mid-1980s and the reconstruction policy that produced weak growth and high government indebtedness.